Sustainability Literacy of Student’s Junior High School at Science Learning in Schools - Adam, Wahyuni; Permanasari, Anna; Hamidah, Ida (Jurnal Pendidikan MIPA, 2021)
This article aims to see whether science learning contributes to the sustainable literacy of junior high school students in school. The method used in this research is the pre experimental method. The instrument used is 15 multiple choice questions. The sample used in this study was 32 students of class IX SMP Negeri 3 Watampone. The overall N-Gain score is 0.29 in the low category. While Ngain in terms of economic aspects 0,4 is in the medium category, the social aspect 0,3 is in the medium category, and the environment 0,2 is in the low category. The percentage of sustainability literacy from the Economic aspect is 67.5% in the medium category, 65% in the social aspect in the medium category, and the environmental aspect 55.63% in the medium category. Thus, this study can be concluded that science learning contributes to the sustainability literacy of students in the low category.Keywords: sustainabily literacy, education for sustainable development, science learning. DOI: http://dx.doi.org/10.23960/jpmipa/v22i2.pp206-214